Estudo comparativo da qualidade da água de chuva coletada em cobertura convencional e em telhado verde - Budel, Marcel Aramis (2014)
The study consists of a comparison of the quality of rainwater collected in two distinct ways of catchments: a system composed of a pitched roof with concrete tiles and another consisted of a vegetated flat coverage, as known as green roof. It aims to characterize the systems used in both forms of coverage, to analyze the quality of rainwater captured in the two systems and to monitor the quality of water stored for later use throughout the study in order to verify the efficiency and performance of catchment systems. It also aims to find relations in the involved variables and to present the results in order to establish a qualitative comparison in the performance of two coverages. The study was conducted in two houses located in the northwest region of the city of Curitiba, capital of Paraná. The appointee, house 1, has a pitched roof with concrete tiles, the rainwater that seeps through the roof is first collected by a trough, followed by a vertical duct to the ground level, with a simple filter, then the water is sent into a tank where it is stored for later use in the external faucet where the water is pumped. However, at house 2, with vegetated flat roof, after passing through the green roof the rainwater is driven by vertical ducts to the concrete tank at ground level, then an electric pump represses the water to a reservoir located on the roof, above the green roof ́s level for storage and later use on the external tap. Samples collected in nine events (17/05/2013 to 03/12/2013) were analyzed for pH, turbidity, dissolved oxygen and temperature, they were measured in situ. Chemical oxygen demand (COD), ammonia, nitrite, nitrate and phosphate were sampled and analyzed in the laboratory of Sanitation UTFPR Campus Ecoville. Nevertheless, for the presence of total and fecal coliforms (E. coli), tests were performed on an outsourced laboratory. As for the results obtained, the conventional roof house 1 rainwater had higher quality in turbidity and chemical oxygen demand (COD) parameter, whereas in house 2 the green roof reduced the natural acidity of rainwater. The two covers were effective in the concentration of ammonia and nitrate, though indicated high concentrations of phosphate. Microbiological parameters in neither roofs met the NBR 15.527/2007 quality. Thus, taken due precautions, it is recommend the use of water from roofs, vegetated and conventional, to flush toilets, to irrigate lawns and ornamental plants, to wash vehicles, to clean sidewalks and streets, to clean patios, water mirrors and to industrial uses, as defined in the standards.